Communal Rights vs Regional Development: Pursuing Justice for Comunal Customary Land - Marius Suprianto Sakmaf; Enny Martha Sasea; Atang Suryana; Zulhilmi Bin Paidi; Mira Novana Ardani (Jurnal Pembangunan Hukum Indonesia, 2025)
This study is motivated by conflicts of authority in the management of natural resources, particularly Tanah Ulayat of indigenous communities, which are often inadequately protected in the course of development and resource exploitation, including illegal mining. The primary objective of this research is to examine the position and authority of the state in managing Tanah Ulayat, to identify the legal implications of illegal mining practices on Tanah Ulayat, and to formulate a legal framework that is both just and constitutional. The study employs a normative juridical method combined with a constitutional approach and an indigenous peoples’ rights perspective. The findings reveal a legal vacuum in the protection of Tanah Ulayat, particularly when mining activities are carried out with customary approval but without state authorization. In conclusion, there is an urgent need for a legal framework that is responsive, participatory, and grounded in the principles of simultaneous development and the recognition of communal rights.